A Comparative Study of Hybrid Energy Storage System using Battery and Supercapacitor for Stand-Alone Solar PV System. Issue 1 (1st August 2022) - Uloom, N A; Mansur, T M N T; Ali, R; Baharudin, N H; Abdullah, A M
Abstract: The standalone solar power system has long been used to meet the electrical needs of basic building structures. To counter the natural supply–demand imbalance caused by solar energy, standalone solar PV system often include energy storage devices, primarily lead–acid batteries. Due to lead-acid battery limitations, solar systems often have higher operational costs compared to traditional power systems. It has been discovered that a supercapacitor-battery hybrid energy storage device can be used to prolong the cycle life of a battery system by reducing the charge–discharge stress caused by variable power exchange. This research examines the influence of a supercapacitor on a photovoltaic system that makes use of a hybrid energy storage system that includes both batteries and supercapacitors in order to lessen the stress placed on the batteries. The methodology involves data collection for load profile and meteorological information, designing solar PV system, and simulation using Matlab SIMULINK to study the effect of supercapacitor on battery current of the evaluated system. Three different energy storage system topologies in building applications were simulated, and their ability in managing battery stress was investigated and evaluated. From the result, it is clear that by applying passive HES system, 53% of battery current can be reduced compared to battery-only system and 92% of reduction can be achieved by using semi-active HES system.